Brand Trust On Brand Love In The Automotive Industry : Brand Equity As a Mediating Variable: Kepercayaan Merek dan Kecintaan Merek di Industri Otomotif : Ekuitas Merek sebagai Variabel Mediasi - Allyya Saputra (OGZ Research & Publishing, 2026)
Abstract: This research examines the relationships among brand trust, brand experience, brand equity, and brand love within Indonesia's automotive industry, based on responses from 374 consumers across five regions of Jakarta. Grounded in the Customer-Based Brand Equity (CBBE) framework and emotional branding theory, Objective: This study analyzes direct and mediating effects of brand trust on brand love, with brand equity as the mediating variable. Methodology : Employing a quantitative, causal, and cross-sectional design under a post-positivist paradigm, data were collected through a validated 4-point Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The constructs measured include brand trust (credibility, transparency, consistency, reputation), brand experience (sensory, affective, cognitive, behavioral), brand equity (awareness, association, perceived quality), and brand love (attachment, identification, loyalty, advocacy). Research Results: Findings reveal that brand trust significantly and positively influences brand equity and brand love. Moreover, brand equity partially mediates these relationships, demonstrating its crucial role in translating trust perceptions into emotional attachment. The model showed strong reliability and validity (Cronbach's α > 0.80, AVE > 0.50, CR > 0.85). Keywords : Brand Trust, Brand Equity, Brand Love, Automotive Industry, Jakarta, Emotional Branding